Political Stability and Infrastructure Governance for Sustainable Development: An Institutional Analysis of Local Government Support for Indonesia’s Nusantara Capital City - Andi Nur Fiqhi Utami; Herman Lawelai; Aco Nata Saputra; Achmad Fauzi Kusmin; Citra N Fariaty; Endriady Edy Abidin (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2026)
This study examines how political stability, infrastructure governance, and sustainable development shape West Sulawesi’s role as a supporting region for Indonesia’s Nusantara Capital City, and its alignment with the Sustainable Development Goals (SDGs), particularly SDG 9 (Industry, Innovation and Infrastructure) and SDG 11 (Sustainable Cities and Communities). Using a sequential mixed-methods design, it triangulates policy documents, interviews, and 100 news articles coded in NVivo 12 Plus. Findings indicate that infrastructure development, especially roads, ports, and energy systems, is the strongest policy driver, reinforced by local government coordination and public–private partnerships. Institutional reliability functions as governance capital, sustaining policy continuity and strengthening accountability. Nevertheless, sustainability integration remains partial, constraining progress towards SDG 9 Targets 9.1 and 9.4 and SDG 11 Targets 11.3, 11.6, and 11.b. Reliance on discourse-based evidence and a cross-sectional timeframe limits causal inference and long-term sustainability assessment. Future research should adopt longitudinal designs, comparative buffer-region analyses, and quantitative sustainability indicators.